Volumetric Properties and Molecular Interactions: Physicochemical Investigations of Synthesized Indolylimidazole Derivatives in Binary DMSO-Methanol Solvent Mixtures - Narendra Nirwan; Chandresh Pareek (International Journal of Scientific Research in Science and Technology, 2025)
Indolylimidazole derivatives are a class of heterocyclic compounds gaining significant attention due to their diverse range of pharmacological activities. However, the fundamental physicochemical properties essential for understanding their behavior in solution and optimizing potential formulations remain underexplored. This study investigates the fundamental physicochemical behavior of newly synthesized indole derivative solutions in binary mixtures of dimethyl sulfoxide (DMSO) and methanol at 303.15 K. Motivated by the significant fluorescent behavior and potential industrial and biological applications of indole scaffolds, this research aims to elucidate the structural interactions and aggregation phenomena within these mixed solvent systems. Precise measurements of density were conducted using an Ostwald’s modified Sprengel pycnometer across a solute concentration range of 0.0001 to 0.01 g•mol•L⁻¹ and varying solvent compositions (25% to 100% DMSO). Subsequent calculations of molar volume and apparent molar volume provided critical thermodynamic data.Analysis of these parameters plotted against concentration revealed distinct Trend Change Points (TCP), indicating the critical concentration for the onset of molecular aggregation or clustering. The results demonstrated that TCP values increase monotonically with higher proportions of DMSO, suggesting that DMSO stabilizes the monomeric form to higher concentrations compared to methanol. Furthermore, investigations into the effect of solvent composition revealed structural breaks at 50% and 75% DMSO, indicating transitions in molecular organization or solvent reorganization as dimerization or trimerization at these specific ratios. Application of the Masson equation to the apparent molar volume data confirmed strong solute-solvent interactions that diminish slightly post-aggregation, alongside complex variations in solute-solute interactions, particularly around the 50% DMSO transition point. These findings establish that the solution behavior of these derivatives is highly dependent on both concentration and solvent ratio, providing essential baseline data for their potential formulation in future applications.
Keywords: Indolylimidazole; Intermolecular Interactions; Physicochemical Properties